2014
DOI: 10.1057/grir.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effects of Risk Classification Bans

Abstract: Risk classification refers to the use of observable characteristics by insurers to group individuals with similar expected claims, to compute the corresponding premiums, and thereby to reduce asymmetric information. Permitting risk classification may reduce informational asymmetry-induced adverse selection and improve insurance market efficiency. It may also have undesirable equity consequences and undermine the implicit insurance against reclassification risk, which legislated restrictions on risk classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…We have shown that loss coverage can be reconciled with (although it is not the same as) an 'equal-weights' utilitarian social welfare, in the spirit of Hoy (2006) or Dionne & Rothschild (2014). Specifically, if insurance demand is iso-elastic, ranking risk classification schemes by loss coverage always gives the same ordering as ranking by social welfare.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have shown that loss coverage can be reconciled with (although it is not the same as) an 'equal-weights' utilitarian social welfare, in the spirit of Hoy (2006) or Dionne & Rothschild (2014). Specifically, if insurance demand is iso-elastic, ranking risk classification schemes by loss coverage always gives the same ordering as ranking by social welfare.…”
Section: Discussionmentioning
confidence: 94%
“…The loss coverage literature contrasts with economic literature on insurance risk classification, as summarised in surveys such as Hoy (2006), Einav & Finkelstein (2011) and Dionne & Rothschild (2014). Economic literature typically takes a utility-based approach: representative agents from each risk-group make purchasing decisions which maximise their expected utilities, and the outcomes of different risk classification schemes are then evaluated by a social welfare function which is a (possibly weighted) sum of expected utilities over the whole population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proposition 2 demonstrates that asymmetric information about risk type interacts with the fraud externality. Complete unraveling is more commonly observed under so‐called fixed contracts (see Dionne and Rothschild, ) when insurers compete in prices for a prespecified indemnity (see Einav and Finkestein, ; Peter, Richter, and Steinorth, ). Ex post moral hazard induces an implicit premium loading, which allows for complete unraveling in our model.…”
Section: Adverse Selectionmentioning
confidence: 99%
“…Risk classification is a traditional and effective tool to reduce adverse selection; however, in various jurisdictions, risk classification based on certain risk factors (e.g., gender) is banned. Schmeiser et al (2014) and Dionne and Rothschild (2014) discuss the potential consequences of such bans, and both suggest that such restrictions result in significant costs.…”
Section: Risk Valuationmentioning
confidence: 99%